2020
DOI: 10.9745/ghsp-d-19-00330
|View full text |Cite
|
Sign up to set email alerts
|

Unmet Need for Family Planning and Experience of Unintended Pregnancy Among Female Sex Workers in Urban Cameroon: Results From a National Cross-Sectional Study

Abstract: Female sex workers (FSWs) in Cameroon have unmet need for effective contraception, and experience of unintended pregnancy and pregnancy termination is common. Reducing barriers to accessing high-quality, voluntary family planning services in FSW-focused community services is a key strategy to promote clientcentered care, promote informed choice, reduce unintended pregnancies, and improve quality of life for FSWs. Résumé en français à la fin de l'article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 79 publications
2
24
0
Order By: Relevance
“…Sub-Saharan Africa was at the epicenter of the epidemic and continues to carry the full brunt of its health and socioeconomic impact due to resistance to condom use that was found to be strongly related to STIs (including HIV/AIDS). 16 Condom use in such relationships may be seen as a clear sign of infidelity. These attitudes represent a major obstacle to the use of condoms as a dual method of protection.…”
Section: Introductionmentioning
confidence: 99%
“…Sub-Saharan Africa was at the epicenter of the epidemic and continues to carry the full brunt of its health and socioeconomic impact due to resistance to condom use that was found to be strongly related to STIs (including HIV/AIDS). 16 Condom use in such relationships may be seen as a clear sign of infidelity. These attitudes represent a major obstacle to the use of condoms as a dual method of protection.…”
Section: Introductionmentioning
confidence: 99%
“…The reluctance of health care workers to provide care to FSWs and avoidance of health services by FSWs is prevalent in sub–Saharan Africa [ 9 , 14 , 63 , 64 ]. A qualitative study in Kenya identified long waiting time, user fees and inconvenient operating hours as factors that impede contraceptive access [ 65 ] whereas in Cameroon, experiences of health-care related stigma was common among FSWs using non-barrier contraception [ 6 ] . To reduce stigma and discrimination against sex workers in clinical settings, health care workers should be engaged in sensitization meetings to raise awareness of FSWs’ needs and the hardship they face, in order to reduce vulnerability when seeking care.…”
Section: Discussionmentioning
confidence: 99%
“…Female sex workers (FSWs) have a higher unmet need for contraceptives compared to women in the general population [1,2]-which is evident from the high rate of unintended pregnancies [3][4][5][6], high abortion rates [4,[6][7][8] and a great desire to prevent future pregnancies [9,10]. In Tanzania, the incidence of unintended pregnancy among FSWs ranges from 12 to 18 per 100 years of exposure [11,12], although it is slightly lower than the incidence in other lower and middle income countries of 27 per 100 years of exposure [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These further suggest a big gap in LARC use among FSWs and threaten future fertility of FSWs who still desire to have children (11). Majority of the key population programs in LMICs target HIV services with little attention and resources accorded to the sexual reproductive health of FSWs (12)(13)(14)(15). Subsequently, HIV preventive packages like condoms have seen a drastic improvement in availability and coverage.…”
Section: Introductionmentioning
confidence: 99%